TORCH, Anti-cardiolepin, and Anti-phospholipids in Women with Repeated Miscarriage in Mosul City - Aldabbagh, Karam A.; Alnori , Mohammed KJ.; Almola, Khalid W. (Open Access Macedonian Journal of Medical Sciences, 2022)
Abstract Background and Objective: The present study aimed to identify a connection between common viral infections and women who had repeatedly miscarriages. Material and Methods: This study is a retrospective study which has been carried out on 2010 records in Mosul city/Iraq, and the patients were all women of child-bearing age (20-35 years old). All of the women had suffered from an abortion at least once before. The target viruses in charge for this study include; Toxoplasma gundi, Cytomegalovirus, Rubella virus, and Herpes virus. Results and Conclusion: The analysis is based on the detection of the anti-bodies which confirmed a negative correlation between antibodies level and active viral infection, together with no clear association between the presence of active infectious status and miscarriage. Additionally, only few positive cases for each individual patient were positive for viral infection. Hence, the outcome confirmed no clear association between presence of infectious agent and repeated miscarriage. Nonetheless, rubella and cytomegalovirus have shown the highest contribution in this regard.